Transition-metal-free regioselective hydroamination of styrenes with amino-heteroarenes. Issue 60 (7th July 2022) - Meena, Priyanka; Ayushee,; Patel, Monika; Verma, Akhilesh K.
Abstract : The base-mediated anti-Markovnikov hydroamination of functionally varied styrenes with amino-substituted pyridine, quinoline, pyrimidine, pyrazine, and phenanthridine with excellent regioselectivity has been described. Abstract : The base-mediated anti-Markovnikov hydroamination of functionally varied styrenes with amino-substituted pyridine, quinoline, pyrimidine, pyrazine, and phenanthridine with excellent regioselectivity has been described. Double hydroamination was observed chemoselectively on the secondary amine, leaving the primary amine intact. Experimental evidence suggests that the proposed reaction involves the nucleophilic addition of the aminopyridyl radical onto vinyl arenes via a single electron transfer.